PENGARUH RELAKSASI BENSON TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI - Darmawan, I Ketut Eri (Coping: Community of Publishing in Nursing, 2015)
An estimated one billion people around the world were suffered from hypertension, while in Indonesia the figure reached 32 percent in 2008 with over 25 years of age range. Benson relaxation can reduce stress, lower blood pressure, lower pulse rate and breathing, and relax the muscles. By the time someone in a relaxed state, stimulation of the sympathetic nerve activity is reduced and the body will reduce the secretion of the hormone cortisol, epinephrine, and noreprineprin where this state can lower blood pressure. This study aims to determine the effect of relaxation benson on blood pressure in patients with hypertension in the Health Center II East Denpasar. This study was a quasi-experimental study (one-group pretest-posttest design). Sample consisted of 30 respondents were selected by purposive sampling. The results of wilcoxon signed rank test was statistically significant with a significance level of p = 0.000 (p value less than ?=0,05), its mean there were differences in systolic and diastolic blood pressure in hypertensive patients before and after administration of benson relaxation. This study suggested to the nurse to use relaxation benson for non pharmacological management in hypertensive patients
Keywords: Hypertension; benson relaxation; non pharmacological therapy